Fire Test Performance 1970
DOI: 10.1520/stp44717s
|View full text |Cite
|
Sign up to set email alerts
|

Fire Tests of Concrete Members: An Improved Method for Estimating Thermal Restraint Forces

Abstract: An earlier exploratory study on the effects of restraint of thermal expansion on the fire resistance of prestressed concrete showed that for similar specimens, made of normal weight concrete, maximum thermal thrust was a function of the allowed linear expansion. In the present study, data were obtained for three additional groups of specimens: lightweight prestressed, lightweight reinforced, and normal weight reinforced. A method is presented for estimating the maximum thermal thrust that occurs during a fire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Fire tests of restrained floor slabs at the PCA furnace [7,8] have shown that the line of thrust moves from below the depth of the slab and towards the centroidal axis during the course of the fire.…”
Section: Position Of Line Of Thrust At the Supportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fire tests of restrained floor slabs at the PCA furnace [7,8] have shown that the line of thrust moves from below the depth of the slab and towards the centroidal axis during the course of the fire.…”
Section: Position Of Line Of Thrust At the Supportsmentioning
confidence: 99%
“…The external thrust from the restraining structure replaces the function of the prestressing in the tendons and maintains the prestressing effect until some of the tendons reached temperatures which would have caused unrestrained beams to collapse. Issen et al [7] showed that almost any amount of restraint greatly enhanced the fire resistance of the slabs as they were able to support their loads considerably longer than for the simply supported condition. Based on these tests conducted at the Portland Cement Association (PCA), a step-by-step method was developed to determine the amount of thrust required to prevent collapse of the floor system, and the required stiffness of the surrounding structure to provide that level of restraint [11].…”
Section: Past Researchmentioning
confidence: 99%
“…Information on T and d T is based on experimental research by Issen, Gustaferro and Carlson (1970). The experimental program consisted of 40 standard fire resistance tests conducted by the Portland Cement Association.…”
Section: Commentary/appendixmentioning
confidence: 99%
“…Nevertheless, the thrust is generally great enough to increase the fire resistance significantly. In most fire tests of restrained assemblies, the fire resistance is determined by temperature rise of the unexposed surface rather than by structural considerations, even though the steel temperatures often exceed 800°C (1500°F) (Abrams et al 1976, Lin and Abrams 1983, Issen et al 1970.…”
Section: Fire Resistance Of Floor Slabs and Roofs Subjected To Thermalmentioning
confidence: 99%